Engineering fluid mechanics - Crowe, C. T.; Elger, D. F.; Roberson, John A. (Hoboken, NJ : Wiley, 2002)
"Fluid Mechanics Solutions by JustAsk! is a web-based tutorial that walks you step-by-step through solutions to selected problems from Engineering Fluid Mechanics, Eighth Edition, while highlighting the important concepts needed to solve each problem. With Fluid Mechanics Solutions by JustAsk!, you'll save valuable time in your studies and build strong problem-solving skills."--BOOK JACKET.
Registration to Web site on 1 leaf in pocket.
0
0
0
0
0
Keywords: Fluid mechanics; NUST